Pattern Reconfigurable Wideband Stacked Microstrip Patch Antenna for 60 GHz Band - Alexander Bondarik; Daniel Sjöberg (International Journal of Antennas and Propagation)
A beam shift method is presented for an aperture coupled stacked microstrip antenna with a gridded parasitic patch. The gridded parasitic patch is formed by nine close coupled identical rectangular microstrip patches. Each of these patches is resonant at the antenna central frequency. Using four switches connecting adjacent parasitic patches in the grid, it is possible to realize a pattern reconfigurable antenna with nine different beam directions in broadside, H-plane, E-plane, and diagonal planes. The switches are modeled by metal strips and different locations for strips are studied. As a result an increase in the antenna coverage is achieved. Measurement results for fabricated prototypes correspond very well to simulation results. The antenna is designed for 60 GHz central frequency and can be used in high speed wireless communication systems.